Effect of Quercetin Rich Onion Extracts on Bacterial Quorum Sensing - Quecan, B. X. V.; Santos, J. T. C.; Rivera, M. L. C.; Hassimotto, N. M. A.; Almeida, F. A.; Pinto, U. M. (Frontiers in Microbiology, 2019)
Quorum sensing (QS) regulates bacterial gene expression and studies suggest quercetin, a flavonol found in onion, as a QS inhibitor. There are no studies showing the anti-QS activity of plants containing quercetin in its native glycosylated forms. This study aimed to evaluate the antimicrobial and anti-QS potential of organic extracts of onion varieties and its representative phenolic compounds quercetin aglycone and quercetin 3-β-D-glucoside in the QS model bacteria Chromobacterium violaceum ATCC 12472, Pseudomonas aeruginosa PAO1 and Serratia marcescens MG1. Three phenolic extracts were obtained: red onion extract in methanol acidified with 2.5% acetic acid (RO-1), white onion extract in methanol (WO-1) and white onion extract in methanol ammonium (WO-2). Quercetin 4-O-glucoside and quercetin 3,4-O-diglucoside were identified as the predominant compounds in both onion varieties using HPLC-DAD and LC-ESI-MS/MS. However, quercetin aglycone, cyanidin 3-O-glucoside and quercetin glycoside were identified only in RO-1. The three extracts showed minimum inhibitory concentration (MIC) values equal to or above 125 μg/ml of dried extract. Violacein production was significantly reduced by RO-1 and quercetin aglycone, but not by quercetin 3-β-D-glucoside. Motility in P. aeruginosa PAO1 was inhibited by RO-1, while WO-2 inhibited S. marcescens MG1 motility only in high concentration. Quercetin aglycone and quercetin 3-β-D-glucoside were effective at inhibiting motility in P. aeruginosa PAO1 and S. marcescens MG1. Surprisingly, biofilm formation was not affected by any extracts or the quercetins tested at sub-MIC concentrations. In silico studies suggested a better interaction and placement of quercetin aglycone in the structures of the CviR protein of C. violaceum ATCC 12472 than the glycosylated compound which corroborates the better inhibitory effect of the former over violacein production. On the other hand, the two quercetins were well placed in the AHLs binding pockets of the LasR protein of P. aeruginosa PAO1. Overall onion extracts and quercetin presented antimicrobial activity, and interference on QS regulated production of violacein and swarming motility.